Intra-Operative and Post-Operative Impact of Body Weight on Total Hip Arthroplasty: Are We Approaching It Correctly? - Edoardo Ipponi; Sara Barderi; Elena Bechini; Belinda Misso; Luca Orsetti; Lorenzo Andreani; Nicola Piolanti; Enrico Bonicoli; Paolo Domenico Parchi (Acta Medica)
Background: To this date, the impact of body weight on total hip arthroplasty is still debated. The literature lacks evidence on the impact of body weight on surgical times and complications. Methods: We retrospectively evaluated all the patients who underwent primary total hip arthroplasty (THA), collecting patients’ pre-operative BMI before surgery. We recorded the surgical approach performed (anterior or posterolateral), and their duration. All the major complications were recorded. Results: Seven-hundred-thirty-two cases were included (627 posterolateral and 105 anterior approach). The mean BMI was 27.3. The mean surgical time was 90.8 minutes (104.9 for anterior and 88.5 for posterolateral approach). We found a significant positive relationship between BMI and surgical times for both cases treated with a posterolateral approach, and (even more remarked) in case anterior approach. Thirty-nine cases (5.3%) had major complications; 27 of them (69.2%) were overweight or obese. The surgical times of those who had complications were significantly higher compared to others. Conclusions: Patients’ body weight, and in particular their Body Mass index, has a direct impact on the duration of THA surgical procedures, particularly if performed using an anterior approach, and an indirect effect on complication rates.